Erratum to “Dielectric-Grating-Coupled Surface Plasmon Resonance From the Back Side of the Metal Film for Ultrasensitive Sensing” - Shaohua Pi; Xie Zeng; Nan Zhang; Dengxin Ji; Borui Chen; Haomin Song; Alec Cheney; Yun Xu; Suhua Jiang; Dalin Sun; Yun Song; Qiaoqiang Gan (IEEE Photonics Journal, 2016)
Presents corrections to figures from the paper, "Dielectric-grating-coupled surface plasmon resonance from the back side of the metal film for ultrasensitive sensing,” (Pi, S. et al.) IEEE Photon. J., vol. 8, no. 1, Feb. 2016, Art. no. 4800207.